Effects of swimming training on blood pressure and vascular function in adults >50 years of age - Nualnim, N.; Parkhurst, K.; Dhindsa, M.; Tarumi, T.; Vavrek, J.; Tanaka, H. (The American Journal of Cardiology, 2012)
Swimming is ideal for older adults because it includes minimum weight-bearing stress and decreased heat load. However, there is very little information available concerning the effects of regular swimming exercise on vascular risks. We determined if regular swimming exercise would decrease arterial blood pressure (BP) and improve vascular function. Forty-three otherwise healthy adults >50 years old (60 ± 2) with prehypertension or stage 1 hypertension and not on any medication were randomly assigned to 12 weeks of swimming exercise or attention time controls. Before the intervention period there were no significant differences in any of the variables between groups. Body mass, adiposity, and plasma concentrations of glucose and cholesterol did not change in either group throughout the intervention period. Casual systolic BP decreased significantly from 131 ± 3 to 122 ± 4 mm Hg in the swimming training group. Significant decreases in systolic BP were also observed in ambulatory (daytime) and central (carotid) BP measurements. Swimming exercise produced a 21% increase in carotid artery compliance (p <0.05). Flow-mediated dilation and cardiovagal baroreflex sensitivity improved after the swim training program (p <0.05). There were no significant changes in any measurements in the control group that performed gentle relaxation exercises. In conclusion, swimming exercise elicits hypotensive effects and improvements in vascular function in previously sedentary older adults.